2016
DOI: 10.15244/pjoes/60722
|View full text |Cite
|
Sign up to set email alerts
|

How Location Shapes Environmental Awareness Among Inhabitants of Eastern Poland – An Empirical Study

Abstract: Environmental awareness and its perception by humans is not an entirely clear issue, and the extent to which problems related to ecology and environmental protection are recognized raises many doubts. Our paper presents fi ndings obtained from the authors' own questionnaire made up of 46 statements carrying positive connotations. A fi ve-level Likert scale was applied to evaluate statements; respondents were asked to specify which level on the scale best corresponded with their view on each statement. In order… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 17 publications
0
7
0
Order By: Relevance
“…When controlling for socio-economic variables, there were no rural-urban differences in China (Liu et al, 2020) and in Pakistan rural residents were more environmentally concerned than urban residents (Ergun et al, 2021). Moreover, rural residents in Poland (Piekarski et al, 2016) and Spain (Berenguer et al, 2005) reported concerns about local environmental problems like water shortages, while urban residents reported abstract environmental concerns like climate change. People living in rural areas may hold more anthropocentric environmental concerns (protect the environment to fulfill human needs), while urban residents may have more ecocentric concerns (protect the environment for its own sake) (Gagnon Thompson & Barton, 1994;Huddart-Kennedy et al, 2009;Rauwald & Moore, 2002).…”
Section: Rural-urban Differencesmentioning
confidence: 90%
“…When controlling for socio-economic variables, there were no rural-urban differences in China (Liu et al, 2020) and in Pakistan rural residents were more environmentally concerned than urban residents (Ergun et al, 2021). Moreover, rural residents in Poland (Piekarski et al, 2016) and Spain (Berenguer et al, 2005) reported concerns about local environmental problems like water shortages, while urban residents reported abstract environmental concerns like climate change. People living in rural areas may hold more anthropocentric environmental concerns (protect the environment to fulfill human needs), while urban residents may have more ecocentric concerns (protect the environment for its own sake) (Gagnon Thompson & Barton, 1994;Huddart-Kennedy et al, 2009;Rauwald & Moore, 2002).…”
Section: Rural-urban Differencesmentioning
confidence: 90%
“…When controlling for socio-economic variables, there were no rural-urban differences in China (Liu et al, 2020) and in Pakistan rural residents were more environmentally concerned than urban residents (Ergun et al, 2021). Moreover, rural residents in Poland (Piekarski et al, 2016) and Spain (Berenguer et al, 2005) reported concerns about local environmental problems like water shortages, while urban residents reported abstract environmental concerns like climate change. People living in rural areas may hold more anthropocentric environmental concerns (protect the environment to fulfill human needs), while urban residents may have more ecocentric concerns (protect the environment for its own sake) (Gagnon Thompson & Barton, 1994; Huddart-Kennedy et al, 2009; Rauwald & Moore, 2002).…”
Section: Rural-urban Differencesmentioning
confidence: 99%
“…Further, the other factors, which appear during transportation, such as movement of transport means (wagons, containers, cargo etc. ), have to be considered, as well, [24][25]. That influences the running properties of a train-set, safety of transportation, dynamics of individual vehicles in a train-set, braking distances and other factors, which relate with the investigated issue [26][27][28][29].…”
Section: Object Of the Researchmentioning
confidence: 99%